Design of a dual‐polarized reflect‐transmit‐array. Issue 2 (4th November 2019) - Xi, Baokun; Xue, Qianzhong; Cai, Yang; Wang, Yong; Yang, Shaopeng; Zhang, Rui; Zhang, Lianzheng
Abstract: A new low‐profile, dual‐polarized reflect‐transmit‐array antenna which combines the linearly polarized reflectarray (RA) and circularly polarized transmitarray (TA) with a shared aperture is proposed. The antenna adopts a three‐parallel dipole and a two‐surface dipole connected by vias as radiating elements in RA and TA design, respectively. By using the polarized grid, TA is decoupled from RA, which greatly enhanced the efficiency and significantly simplified the whole design process. To minimize the overall thickness, the TA employs double metal layer with two vias instead of multilayer structures. The operating mechanism of the TA layer is then analyzed by characteristic mode analysis. An array prototype with a 256‐mm circular aperture was fabricated and experimentally verified. The measured gains in reflect mode and transmit mode is 27.5 dB with 54.3% aperture efficiency and 26.7 dB with 45.1% aperture efficiency, respectively. This prototype confirms the feasibility of designing a low‐profile, multifunctional, wideband, and high‐efficiency reflect‐transmit array.